Pengaruh Kinerja Keuangan dan GCG Terhadap Nilai Perusahaan Dengan Struktur Modal Dan Kebijakan Dividen Sebagai Variabel Moderasi - Maghdalena Sihaloho, Yolanda; Hwihanus (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to analyze the influence of financial performance and Good Corporate Governance (GCG) on firm value with capital structure and dividend policy as moderating variables. The research employs a quantitative descriptive method using secondary data from annual financial reports of textile companies listed on the Indonesia Stock Exchange for the period 2019-2023. Sampling was conducted using purposive sampling method. Data analysis was performed using PLS-SEM with SmartPLS. The results show that financial performance, GCG, capital structure, and dividend policy have no significant effect on firm value. Capital structure and dividend policy as moderating variables also do not prove to moderate the relationship between financial performance and GCG on firm value. These findings indicate the possibility of other factors having more influence on firm value that are not covered in this study.